PENINGKATAN HASIL BELAJAR PESERTA DIDIK MELALUI PENDEKATAN PERMAINAN PADA PEMBELAJARAN PJOK DI KELAS X SMAN 2 PACITAN TAHUN 2023/2024 - Nisa', Alvi Zuhrotun; Juandini, Amellina; Faishal Huda, Faiz; Wibowo, Sapto; Sukatman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to determine the improvement in student learning outcomes through a project based learning approach in class X PJOK learning at SMAN 2 Pacitan 2023/2024. This research is Classroom Action Research (PTK). This research was carried out in two cycles, each cycle consisting of planning, implementation, observation and reflection. The subjects in this research were class X students at SMAN 2 Pacitan. Data sources come from teachers, students and researchers. Data collection techniques use observation and documentation. Data validity uses data triangulation techniques. Data analysis uses qualitative descriptive techniques using percentage techniques to see trends that occur in learning activities. Based on the research results, it can be concluded that there has been an increase through efforts to improve student learning outcomes through a project based learning approach in class X PJOK learning at SMAN 2 Pacitan in 2023/2024.